The Dynamics of Madrasah in North Sumatra in The Reform Time (1998-2021) - Khairury Hafiza; Zaini Dahlan (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Madrasah is an institution under the auspices of the Ministry of Religion. The existence of madrasas is one of the saviours in advancing education in Indonesia, especially for madrasa education in North Sumatra. Madrasas are also formal educational institutions with a curriculum like public schools, but madrasas have particular advantages: Islamic religious subjects are studied in more detail than public schools. Various challenges have become a long process from ancient times to the reformation period felt by the ministry of religion and society in generating madrasa progress. Therefore, this article aims to determine the dynamics of madrasas in North Sumatra. In this article, using a qualitative method, the type of case study method is exploring a case about a particular matter by involving gathering information from various related sources, searching related journal literature and interviews with multiple sources of information such as school principals, communities and students within the scope of madrasas. That way, the desired information will be obtained quickly and directed as aimed. The research was used to collect data and information regarding related problems as determined. This article shows that the development of madrasas in North Sumatra has made a lot of progress from time to time, such as the implementation of plus skills madrasas, adiwiyata madrasas and IT-based madrasas. With various superior programs owned by madrasas, the development of madrasas will develop and progress.